Study of Physical and Mechanical Properties of Knitted Fabrics - Shamsiddinova Umida Rustambek qizi; Dadamirzaeva Shakhlo Makhamadali qizi; Khojimatova Durdona Adkhamjon qizi; Rahmatova Sadokat Umarjonovna; Kholikov Kurbonali Madaminovich (Research Parks Publishing LLC, 2022)
In this article, the analysis of the physical and mechanical parameters of knitted fabrics intended for the production of an assortment of upper knitted products obtained on a 28-class Mayer machine is made, and recommendations for various assortments are based on it.